Is heavy eccentric calf training superior to wait-and-see, sham rehabilitation, traditional physiotherapy and other exercise interventions for pain and function in mid-portion Achilles tendinopathy? - Murphy, M.; Travers, Mervyn; Gibson, W. (2018)
Background: Mid-portion Achilles tendinopathy (AT) is prevalent amongst athletic and non-athletic populations with pain, stiffness and impaired function typically reported. While different management options exist, loading protocols remain the best available intervention and have been shown to be effective in the management of AT. Trials investigating loading in AT have used a variety of different protocols, and recent narrative reviews suggest that no protocol is superior to another when comparing outcomes in pain and function. However, there has been no systematic review or meta-analysis completed to determine this. Furthermore, the narrative review did not consider wait-and-see or sham interventions, thus a systematic review and met-analysis which includes wait-and-see or sham interventions is warranted. Methods: A systematic review and meta-analyses will be conducted as per the PRISMA guidelines. The databases PUBMED, CINAHL (Ovid) and CINAHL (EBSCO) will be searched for articles published from inception to 31 December 2017. Our search focuses on studies examining the improvement of pain and function when completing a loading program for mid-portion AT. Only randomised/ quasi-randomised trials will be included while case reports and case series will be excluded. The primary outcome assessing pain and function will be the Victorian Institute Sports Assessment - Achilles (VISA-A). Two reviewers will screen articles, extract data and assess the risk of bias independently with a third reviewer resolving any disagreements between the two reviewers. A meta-analysis will then be performed on the data (if appropriate) to determine if the traditional heavy load calf training protocol described by Alfredson is superior to wait-and-see, sham intervention, traditional physiotherapy, and other forms of exercise rehabilitation. Discussion: This systematic review and meta-analysis will allow us to investigate if there are difference in pain and function when comparing wait-and-see, sham interventions, traditional physiotherapy and different exercise interventions to the traditional heavy eccentric calf training protocol for mid-portion Achilles tendon pain.